Development and validation of iloperidone by UV spectrophotometric methods - C.Sivakumari; D.Amitha; A. Gopi Reddy; Ramangineyulu (International Journal of Pharmacy and Analytical Research, 2016)
A simple, accurate and economical UV visible spectrophotometric method has been developed for evaluation of Iloperidone drug. The standard and sample solutions were prepared by using distilled water as a solvent. Quantitative determination of the drug was performed at wavelength range 220 nm. The linearity was established over the concentration range of 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 μg/ml for Iloperidone with correlation coefficient value of 0.9997. Precision studies showed that % relative standard deviation was within range of acceptable limits. The mean percentage recovery was found to be 98.9%. The proposed method has been validated as per ICH guidelines. has been validated as per ICH guidelines.